Faktor Frekuensi Kunjungan Lansia Ke Posyandu Lansia Di Kecamatan Pontianak Timur - Iskandar Arpan; Sunarti Sunarti (Jurnal Vokasi Kesehatan, 2017)
Abstract: Factor Of Elderly Frequency Visits In Elderly Integrated Service Post Of East Pontianak District. Indonesia’s elderly population has increased but their health condition is still considered low. In this regard, the government has conducted a special program, namely IHC for elderly, in certain areas and run by the local community, so that they can get health care easily. However, the frequency of the elderly health visit still lows with an average visit of 41.76%. This number is still far from the target that has been set by the Health Department (80%). This study aimed to determine factors of elderly frequency visit the in integrated health care centre of East Pontianak district. Using cross-sectional approach, 75 respondents participated as the samples. They were selected by using purposive sampling technique. The data were statistically analyzed by using chi-square test. The study revealed that there was a correlation of elderly knowledge (p=0,035), family support (p= 0,024) with elderly frequency in visiting the integrated service post centre of East Pontianak district. The variables that didn’t correlate with elderly frequency in visiting the integrated service post centre were elderly perception and distance. From the findings, health workers need to encourage the elderly to be more active in visiting the health center.Abstrak: Faktor Frekuensi Kunjungan Lansia Ke Posyandu Lansia Di Kecamatan Pontianak Timur. Jumlah penduduk lansia di Indonesia telah meningkat dan kesehatan lansia masih rendah, pemerintah mengadakan program khusus yaitu Posyandu Lansia di daerah tertentu yang telah disepakati, yang digerakkan oleh masyarakat di mana mereka bisa mendapatkan pelayanan kesehatan. Namun, frekuensi kunjungan lansia ke Posyandu di beberapa posyandu masih rendah dengan rata-rata kunjungan yaitu, 41,76% hal ini masih jauh dari target yang telah di tetapkan oleh dinas kesehatan yaitu 80%. Tujuan penelitian untuk mengetahui faktor yang berhubungan dengan frekuensi kunjungan lansia ke posyandu lansia di Kecamatan Pontianak Timur. Metode penelitian dengan desain Cross Sectional, Sampel sebanyak 75 responden diambil dengan teknik purposive sampling. Teknik analisis data dengan menggunakan uji statistik chi-sqaure. Hasil penelitian ada hubungan antara pengetahuan lansia (p=0,035, dukungan keluarga (p= 0,024) dengan frekuensi (keteraturan) kunjungan lansia ke posyandu lansia. faktor yang tidak berhubungan antara lain persepsi lansia, jarak. Disarankan kepada petugas kesehatan atau Puskesmas untuk terus meningkatkan sosialisasi dan motivasi untuk para lansia agar lebih aktif berkunjung ke posyandu lansia.